Review article: A primer for clinical researchers in the emergency department: Part XII. Sustainability of improvements in care: An introduction. (2nd August 2022) - Ramsden, Victoria; Middleton, Sandy; McInnes, Elizabeth; Babl, Franz E; Tavender, Emma
Abstract: Despite an increased focus on ways to improve implementation of evidence and de‐implementation of practices with no known benefit, there is limited guidance on how to sustain these improvements. This review provides an introduction to sustainability of improvements in care and sustainability research, discussing how to support sustainability in practice and detailing a sustainability research agenda for the emergency medicine setting.